Post-transcriptional modulation of cytochrome P450s, Cyp6g1 and Cyp6g2, by miR-310s cluster is associated with DDT-resistant Drosophila melanogaster strain 91-R - Keon Mook Seong (Nature Portfolio, 2020)
Abstract The role of miRNAs in mediating insecticide resistance remains largely unknown, even for the model species Drosophila melanogaster. Building on prior research, this study used microinjection of synthetic miR-310s mimics into DDT-resistant 91-R flies and observed both a significant transcriptional repression of computationally-predicted endogenous target P450 detoxification genes, Cyp6g1 and Cyp6g2, and also a concomitant increase in DDT susceptibility. Additionally, co-transfection of D. melanogaster S2 cells with dual luciferase reporter constructs validated predictions that miR-310s bind to target binding sites in the 3ʹ untranslated regions (3ʹ-UTR) of both Cyp6g1 and Cyp6g2 in vitro. Findings in the current study provide empirical evidence for a link between reduced miRNA expression and an insecticidal resistance phenotype through reduced targeted post-transcriptional suppression of transcripts encoding proteins involved in xenobiotic detoxification. These insights are important for understanding the breadth of adaptive molecular changes that have contributed to the evolution of DDT resistance in D. melanogaster.